The pandemic and consumer cultural theory: a conceptual model with a fifth interest cluster / Seow, Richard Yeaw Chong - Seow, Richard Yeaw Chong (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2022)
Consumer research is cardinal to all types of businesses. Understanding consumer behaviours give organizations competitive advantages in many ways, especially in getting consumers to willingly pay for the products and services continuously. This is the core of all entrepreneurial activities. Traditionally, marketing tends to treat consumers as a group of individuals with homogenous characteristics. While consumers share similarities, consumers do show heterogenous features which make them unique from others. Over the past forty years, there are a mountain of literature that discover consumer behavioural differences due to socio-cultural influence. The Consumer Cultural Theory (CCT) was coined in 2005, organizing past research works in a meaningful fashion to enable a good understanding of consumer behaviours in the respective cultural context. However, the unexpected arrival of the pandemic has created massive disruptions to consumer behaviours, undermining the adequacy of CCT in addressing this new phenomenon. To address this scientific gap, a theoretical conceptual model with Phenomenological Influencer (PI) as the fifth interest cluster is proposed with the intent to give academicians and practitioners useful insights into consumer research and consumer behaviours. Even though some countries have evolved into the endemic stage, the impact of PI is still happening in society, changing consumer behaviours in an unorderly fashion. This model offers academicians and practitioners useful insights to make further scientific investigations to enrich CCT theoretical knowledge.